Courts, Clans and Companies: Mobile Money and Dispute Resolution in Somaliland - Nicole Stremlau (Stability : International Journal of Security and Development, 2015)
One of the world’s most ambitious experiments in mobile money is underway in the Somali territories. In the absence of a strong central government and internationally recognized banking institutions, remittance companies and the telecoms industry have been innovating to provide services unique to the Somali context, which is making the economy increasingly ‘cashless’. Mobile money has posed new regulatory and legal challenges, particularly when disputes involving consumers are involved. This article focuses on a case study from Somaliland (the northern, self-declared independent region of Somalia) and examines Zaad, the dominant mobile money platform. Given the weak state institutions, there are a variety of actors, including private companies, government police and courts, sharia courts and traditional elders that play an active role in resolving conflicts that result from mobile money transactions, forging a hybrid judicial approach. We examine how these different actors intervene and create an enabling environment to allow innovation and foster trust in a region of the world that is frequently characterized as violent and lawless.